2018
DOI: 10.1177/0956797617736886
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Into Literacy: The Role of Early Oral Language Abilities and Family Risk for Dyslexia

Abstract: The present study investigated the role of early oral language and family risk for dyslexia in the two developmental pathways toward reading comprehension, through word reading and through oral language abilities. The sample contained 237 children (164 at family risk for dyslexia) from the Dutch Dyslexia Program. Longitudinal data were obtained on seven occasions when children were between 4 and 12 years old. The relationship between early oral language ability and reading comprehension at the age of 12 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 27 publications
11
56
2
Order By: Relevance
“…The stability of VAS performance was higher than stability estimates reported for phonological skills (e.g., Nation & Hulme, 2011;Wagner, Torgesen, & Rashotte, 1994). Notably, the stability in VAS performance was even close to the exceptionally high stability in reading performance reported in this study and others (e.g., van Viersen et al, 2018). Another main finding concerns the absence of crosslagged effects of VAS on reading, and vice versa.…”
Section: Discussionsupporting
confidence: 68%
“…The stability of VAS performance was higher than stability estimates reported for phonological skills (e.g., Nation & Hulme, 2011;Wagner, Torgesen, & Rashotte, 1994). Notably, the stability in VAS performance was even close to the exceptionally high stability in reading performance reported in this study and others (e.g., van Viersen et al, 2018). Another main finding concerns the absence of crosslagged effects of VAS on reading, and vice versa.…”
Section: Discussionsupporting
confidence: 68%
“…Previous FR studies had shown that FR is a unique predictor of children's RD over and above emergent literacy (Puolakanaho et al, 2007), emergent literacy and oral language skills (Carroll et al, 2014), and children's general IQ, verbal IQ and emergent literacy in kindergarten, reading fluency and accuracy in Grade 2 and 3 (van Viersen et al, 2018). The novel findings from the current multifactorial prediction model extend the existing literature, indicating that FR predicts children's RD at the end of second-grade over and above cognitive factors (emergent literacy) and environmental factors (parents' education and HLE) while accounting for gender, children's interest in literacy and year in kindergarten.…”
Section: Discussionmentioning
confidence: 99%
“…Carroll et al (2014) argued that FR children show additional difficulties in literacy that cannot be fully explained in terms of their language and phonological skills. Furthermore, family risk was found to make an additional contribution in the prediction of Grade 6 reading comprehension after taking into account children's general IQ, verbal IQ, emergent literacy in kindergarten, and reading fluency and accuracy in Grade 2 and 3 (van Viersen et al, 2018). However, none of these studies (Carroll et al, 2014;Puolakanaho et al, 2007;van Viersen et al, 2018) included environmental factors such as parental education level or the HLE in their analyses which might have accounted for some of unexplained variance in literacy skills.…”
Section: Family Risk and Multiple Cognitive Prediction Modelmentioning
confidence: 99%
“…Moreover, compared with preschoolers who are not at familial risk for dyslexia, children at familial risk perform less well on these key predictors . In addition, limited oral language and knowledge of vocabulary put children at risk for subsequent reading impairments , although their effect on word decoding skills is likely mediated by the cognitive predictors of dyslexia .…”
Section: Cognitive Foundations Of Dyslexiamentioning
confidence: 99%